2019
DOI: 10.1007/978-3-030-11548-7_27
|View full text |Cite
|
Sign up to set email alerts
|

Improving Serious Games Analyzing Learning Analytics Data: Lessons Learned

Abstract: Serious games adoption is increasing, although their penetration in formal education is still surprisingly low. To improve their outcomes and increase their adoption in this domain, we propose new ways in which serious games can leverage the information extracted from player interactions, beyond the usual post-activity analysis. We focus on the use of: (1) open data which can be shared for research purposes, (2) real-time feedback for teachers that apply games in schools, to maintain awareness and control of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Yet, this task is almost impossi-ble to carry out, as there are many different SG genres, covering diverse subjects, addressed to different groups of people. As a result, some concluded that the evaluation of SGs' functional components remains unclear (e.g., Alonso-Fernández, Pérez-Colado, Freire, Martínez-Ortiz, & Fernández-Manjón, 2018;Zhonggen, 2019) or that it is biased (e.g., Connolly, Boyle, MacArthur, Hainey, & Boyle, 2012). Others declared that past studies failed to solve this problem (Shi & Shih, 2015) or supported the view that there is no established methodology for measuring their effectiveness (e.g., Hersh & Leporini, 2018;Serrano-Laguna, Manero, Freire, & Fernández-Manjón, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, this task is almost impossi-ble to carry out, as there are many different SG genres, covering diverse subjects, addressed to different groups of people. As a result, some concluded that the evaluation of SGs' functional components remains unclear (e.g., Alonso-Fernández, Pérez-Colado, Freire, Martínez-Ortiz, & Fernández-Manjón, 2018;Zhonggen, 2019) or that it is biased (e.g., Connolly, Boyle, MacArthur, Hainey, & Boyle, 2012). Others declared that past studies failed to solve this problem (Shi & Shih, 2015) or supported the view that there is no established methodology for measuring their effectiveness (e.g., Hersh & Leporini, 2018;Serrano-Laguna, Manero, Freire, & Fernández-Manjón, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In both of these examples described above, players could see leader boards and compare their performance to other students (i.e., the social frame of reference), which may lead to competition rather than knowledge and skill mastery (Alonso-Fernández et al, 2018). In the next section, we discuss an example of a studentfocused LA dashboard in an educational game called Physics Playground, which uses an achievement frame of reference and focuses on mastery, not competition.…”
Section: La Dashboards In Educational Gamesmentioning
confidence: 99%
“…Problems such as the lack of both computational and additional human resources, teacher's rejection of new teaching methods, the fact that some teachers still believe that the implementation of educational games is a complex process that is beyond their reach, make it very difficult to systematically expand the implementation of games in educational settings. That is why providing guidelines and facilitating a simplified deployment of these games is so important, so that their implementation can greatly benefit teachers and students [3]. One of the reported methods to facilitate the adoption of educational games in the classroom is to provide visualization dashboards that can represent easy, interactive and intuitive visualizations, a series of interactions of the student with the environment.…”
Section: Related Workmentioning
confidence: 99%